2021
DOI: 10.1063/5.0036591
|View full text |Cite
|
Sign up to set email alerts
|

Determining the band alignment of copper-oxide gallium-oxide heterostructures

Abstract: The copper oxides cuprite (Cu2O) and tenorite (CuO) are ideal candidates for solar cells as they promise high conversion efficiencies according to the Shockley–Queisser limit. However, both cannot readily be doped n-type, thus hampering the formation of all copper oxide p–n junctions for solar cell applications. The combination of the copper oxides with gallium sesquioxide, in particular, α-Ga2O3 and β-Ga2O3, is considered to be an excellent heterojunction system for overcoming this challenge. In such a p–n ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In figure 6, the XRD peaks corresponding to the Cu(I) oxide (Cu 2 O) and Cu(II) oxide (CuO) phases of copper oxide are clearly observed. All these XRD peaks of copper oxide formation were matched with reported data and Joint Committee on Powder Diffraction Standards(JCPDS) file numbers: #782076, #895899, #770199, #801917, and #895897 [53,54]. Here, G(001), G(002), G(003), and G(004) are the XRD peaks of the Ga 2 O 3 (001) epilayer.…”
Section: Resultsmentioning
confidence: 60%
“…In figure 6, the XRD peaks corresponding to the Cu(I) oxide (Cu 2 O) and Cu(II) oxide (CuO) phases of copper oxide are clearly observed. All these XRD peaks of copper oxide formation were matched with reported data and Joint Committee on Powder Diffraction Standards(JCPDS) file numbers: #782076, #895899, #770199, #801917, and #895897 [53,54]. Here, G(001), G(002), G(003), and G(004) are the XRD peaks of the Ga 2 O 3 (001) epilayer.…”
Section: Resultsmentioning
confidence: 60%
“…They found that α-Ga 2 O 3 /Cu 2 O has the lowest CBO of ~0.2 eV and a VBO of ~3.2 eV, while, in β-Ga 2 O 3 /Cu 2 O junctions, the CBO increases to ~1.3 eV and the VBO to ~3.7 eV. To this respect, they claimed that the use of α-Ga 2 O 3 bears the highest potential for application in solar cells in combination with Cu 2 O [21]. Their work, however, did not show electrical characterization of the junctions.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of technology, people use different synthesis methods to integrate two different metal oxide semiconductor materials to form different structures in order to improve their photoelectric properties. For example, ZnO/Ga 2 O 3 and CuO/Ga 2 O 3 heterostructure UV photodetectors have been reported [19][20][21]. However, the facile fabrication of CuO/β-Ga 2 O 3 nano-heterojunctions and their effects on response performance remains underdeveloped.…”
Section: Introductionmentioning
confidence: 99%